Local wisdom of dayak ethnic groups in central kalimantan, Indonesia - Suswandari, Suswandari; Armiyati, Laely; Azid, Nurulwahida (ETNOSIA : Jurnal Etnografi Indonesia, 2022)
The Dayak ethnicity is the largest community in the Central Kalimantan region, but this ethnic identity is slowly disappearing along with the development of modernization among the younger generation. This study aims mapped sub-ethnic and ethnic groups (sedatuk) and identify the local wisdom of the Dayak ethnic groups that still survive in Central Kalimantan. This study uses a library research approach. The research collects data by reviewing and exploring journals, books, and documents (both printed and electronic) and other relevant data sources. The results show that the Dayak ethnicity in Central Kalimantan is divided into several sub-ethnics, where each sub-ethnic is further divided into kinship clans (sedatuk). Local wisdom that Dayak Ethnic still maintains which are religious and kinship system. Also, value systems are appreciation of nature, communal system, ancestors’ veneration, marriage system, traditional building, art (traditional music, dance, song, weaving art, sculpting, painting, and tattoo), traditional weapon, farming, and agriculture. Local governments can collaborate with private and public institutions to preserve local Dayak ethnic wisdom, especially in the younger generation.